Thymoquinone and madecassoside improve motor function in a rotenone-induced mouse model of early Parkinson’s disease: Role of dopamine, alpha-synuclein and mBDNF - Kusumawati, Shinta; Endharti, Agustina T.; Balafif, Farhad; Kurniawan, Shahdevi N.; Rosidah, Aris; Anaqah, Rabjhany; Barqillah, Izzunazel A.; Khotimah, Husnul (Narra Sains Indonesia, 2025)
Parkinson’s disease is a progressive, incurable neurodegenerative disorder characterized by the degeneration of dopaminergic neurons and pathological aggregation of α-synuclein in the midbrain, leading to motor dysfunction. Thymoquinone (TQ), an active compound from Nigella sativa, has demonstrated antioxidant properties that may reduce dopamine degradation, while madecassoside (MA), a triterpenoid component of Centella asiatica, exhibits neuroprotective effects. To date, no study has investigated the combined effects of TQ and MA in a Parkinson’s disease model. The aim of this study was to evaluate the synergistic neuroprotective potential of TQ and MA on motor function, dopamine levels, α-synuclein accumulation, and mature brain-derived neurotrophic factor (mBDNF) expression in a rotenone (ROT)-induced mouse model of early Parkinson’s disease. Rotenone (2.5 mg/kg BW) was administered subcutaneously for two weeks to induce Parkinson’s disease, while TQ alone, MA alone and combination of TQ and MA at various doses, as well as a reference drug (pramipexole) were given every 48 hours concurrently with rotenone. Motor symptoms were assessed through behavioral tests, including the open field test (OFT), beam walking test, and hanging wire test; midbrain dopamine levels were quantified via enzyme-linked immunosorbent assay (ELISA), α-synuclein expression was assessed using Western blotting, and immunohistochemistry was used to detect mBDNF-positive cells in the cerebral cortex. The combination of TQ and MA significantly increased midbrain dopamine levels and improved locomotor activity, as shown by increased total distance traveled and mean velocity in ROT-induced mice. Biochemically, this combined treatment reduced α-synuclein expression, suggesting attenuation of early pathological aggregation typically observed in Parkinson’s disease. Although the increase in mBDNF expression in the cerebral cortex was not statistically significant, it was higher in the TQ-MA treatment group compared to controls and other groups. Collectively, these results highlight the therapeutic potential of TQ and MA in combination to counteract both motor deficits and early neurochemical disruptions in a ROT-induced model of Parkinson’s disease.